Supramolecular assembly of molecular gold(I) compounds: An evaluation of the competition and complementarity between aurophilic (Au⋯Au) and conventional hydrogen bonding interactions - Tiekink, E.R.T. (Elsevier, 2014)
A bibliographic review of the crystallographic literature has been conducted on gold(I) compounds bearing functional groups capable of forming conventional hydrogen bonding interactions, namely, primary amide, secondary amide and carboxylic acid. The clear majority of structures featured hydrogen bonding interactions leading to well defined zero- or one-dimensional supramolecular architectures; rarely were two-dimensional architectures formed. Conversely, aurophilic, Auâ¯Au, were the exception rather than the rule. This observation is correlated with steric hindrance: small atoms associated via directional hydrogen bonding compared with encumbered gold-atom environments (due to bulky ligands). Amide-â¯HNCO2 and carboxylic acid-â¯HOCO2 synthons featured in significantly more of the gold(I) structures compared with all-organic systems, particularly for non-ionic structures where charged-assisted hydrogen bonding precluded the formation of these cyclic synthons. This suggests a crystal engineering strategy of functionalising metal complexes with hydrogen bonding potential to improve opportunities of rational design of crystal structures. Â© 2014.